2019
DOI: 10.1017/s1355617719000808
|View full text |Cite
|
Sign up to set email alerts
|

Visual versus Verbal Working Memory in Statistically Determined Patients with Mild Cognitive Impairment: On behalf of the Consortium for Clinical and Epidemiological Neuropsychological Data Analysis (CENDA)

Abstract: Objective:Previous research in mild cognitive impairment (MCI) suggests that visual episodic memory impairment may emerge before analogous verbal episodic memory impairment. The current study examined working memory (WM) test performance in MCI to assess whether patients present with greater visual versus verbal WM impairment. WM performance was also assessed in relation to hippocampal occupancy (HO), a ratio of hippocampal volume to ventricular dilation adjusted for demographic variables and intracranial volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, we did not find any significant improvements in other cognitive domains. It could be due to the visual working memory impairment that emerged before the verbal working memory impairment among individuals with MCI as suggested by Emrani et al [ 39 ]. Therefore, the effect of the P. minor extract supplement may be more notable in the visual memory domain as compared to other cognitive domains in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we did not find any significant improvements in other cognitive domains. It could be due to the visual working memory impairment that emerged before the verbal working memory impairment among individuals with MCI as suggested by Emrani et al [ 39 ]. Therefore, the effect of the P. minor extract supplement may be more notable in the visual memory domain as compared to other cognitive domains in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the current research was to determine how well machine analytic techniques could classify AD patients, non-MCI patients, amnestic MCI, and combined mixed/dys MCI patents into their respective subtypes. Prior research has demonstrated that non-MCI and selected MCI subtypes can be differentiated using tests assessing mental manipulation (Emrani et al, 2018), verbal versus visual working memory (Emrani et al, 2019), verbal versus visual episodic memory (Wasserman et al, 2019), and selected visuospatial operations (Wasserman et al, submitted). These data are compelling on the basis of the neurocognitive constructs that are assessed and differentiated between groups.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable interest in the diagnosis and characterization of mild cognitive impairment (MCI), a syndrome believed to be a prodrome often leading to dementia. A variety of MCI subtypes have been identified, including patients presenting with single-domain syndromes such as amnestic (aMCI) and dysexecutive (dys MCI) and a combined or mixed (mixed MCI) phenotype (Emrani et al, 2019;Eppig et al, 2012;Libon et al, 2011). Past research suggests varying rates of conversion to dementia and reversion to normal cognitive functioning depending on MCI subtype (Aerts et al, 2017;Díaz-Mardomingo, García-Herranz, Rodríguez-Fernández, Venero, & Peraita, 2017;Pandya, Lacritz, Weiner, Deschner, & Woon, 2017;Shimada, Doi, Lee, & Makizako, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies documented that performance on span tasks was predictive of conversion to AD at follow‐up 26,27 . Finally, in studies that considered the severity of cognitive impairment, multiple‐domain MCI patients quite consistently obtained reduced span scores with respect to single‐domain amnestic MCI patients 23 …”
Section: Introductionmentioning
confidence: 97%
“…The few studies that focussed on span tests reported quite controversial data, which is likely due to the adoption of discrepant span procedures and variability in the experimental samples recruited. Indeed, although some studies reported significantly lower span scores in MCI patients than healthy controls, especially when span tasks with more demanding procedures were used, 22,23 other studies failed to report significant differences, both for simpler and more complex paradigms 24,25 . Some of these studies documented that performance on span tasks was predictive of conversion to AD at follow‐up 26,27 .…”
Section: Introductionmentioning
confidence: 99%